Using computerised surface wound mapping to compare the potential medical effectiveness of Enhanced Protection Under Body Armour Combat Shirt collar designs. Issue 1 (20th February 2014) - Breeze, John; Allanson-Bailey, L C; Hunt, N C; Delaney, R; Hepper, A E; Lewis, E A
Abstract : Introduction: Protecting the neck from explosively propelled fragments has traditionally been achieved through a collar attached to the ballistic vest. An Enhanced Protection Under Body Armour Combat Shirt (EP-UBACS) collar has been identified as an additional method of providing neck protection but limited evidence as to its potential medical effectiveness exists to justify its procurement. Method: Entry wound locations and resultant medical outcomes were determined using Abbreviated Injury Scale (AIS) for all fragmentation neck wounds sustained by UK soldiers between 01 January 2010 and 31 December 2011. Data were prospectively entered into a novel computerised tool base and comparisons made between three EP-UBACS neck collar designs in terms of predicted reduction in AIS scores. Results: All collars reduced AIS scores, with the greatest reduction provided by designs incorporating increased standoff from the neck and an additional semi-circle of ballistic material underneath the collar at the front and back. Discussion: This technique confirms that reinforcing the neck collar of an EP-UBACS would be expected to reduce injury severity from neck wounds. However, without knowledge of entry wound locations for injuries to other body areas as well as the use of AIS scores without clinical or pathological verification its further use in the future may be limited. The ability to overlay any armour design onto a standardised human was potentially the most useful part of this tool and we would recommend developing this technique using underlying anatomical structures and not just the skin surface.